2016
DOI: 10.3390/ijms17010039
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Kinetic Properties of the Lactate Dehydrogenase Isoenzyme C4 of the Plateau Pika (Ochotona curzoniae)

Abstract: Testis-specific lactate dehydrogenase (LDH-C4) is one of the lactate dehydrogenase (LDH) isozymes that catalyze the terminal reaction of pyruvate to lactate in the glycolytic pathway. LDH-C4 in mammals was previously thought to be expressed only in spermatozoa and testis and not in other tissues. Plateau pika (Ochotona curzoniae) belongs to the genus Ochotona of the Ochotonidea family. It is a hypoxia-tolerant species living in remote mountain areas at altitudes of 3000–5000 m above sea level on the Qinghai-Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…However, the isozyme pattern within a cell would affect how quickly the reaction once again reaches equilibrium if a disturbance should occur (Quistorff & Grunnet, 2011b;Wang et al, 2016). Additionally, even if the reaction is considered close to dynamic equilibrium, the cellular environment is not a closed system.…”
Section: Ldh Isozymes and Expressionmentioning
confidence: 99%
“…However, the isozyme pattern within a cell would affect how quickly the reaction once again reaches equilibrium if a disturbance should occur (Quistorff & Grunnet, 2011b;Wang et al, 2016). Additionally, even if the reaction is considered close to dynamic equilibrium, the cellular environment is not a closed system.…”
Section: Ldh Isozymes and Expressionmentioning
confidence: 99%
“…These findings imply that LDH-C 4 has an affinity for pyruvate that is 60-fold higher than that for lactate, and suggest that pyruvate turnover to lactate may be high even at high concentrations of endogenous or extracellular lactate ( Clausen and Ovlisen, 1965 ; Wilkinson and Withycombe, 1965 ; LeVan and Goldberg, 1991 ; Wong et al, 1997 ). We also found that pika LDH-C 4 had a lower K m for pyruvate (∼0.052 mmol/l) and a higher K m for lactate (∼4.934 mmol/l), and that it was beneficial to catalyse the conversion of pyruvate to lactate even at high concentrations of lactate endogenously ( Wang et al, 2016 ). Those results suggest that the biochemical properties, which separated LDH-C 4 from the other LDH isoforms are conducive to the high glycolytic flux level.…”
Section: Discussionmentioning
confidence: 82%
“…LDH-C 4 is expressed in the spermatozoa and testis of birds and mammals ( Goldberg, 1964 , 1975 , 1984 ; Coonrod et al, 2006 ), and is one of the LDH isoenzymes ( Blanco and Zinkham, 1963 ; Goldberg, 1963 ). LDH-C 4 has higher affinity for pyruvate than lactate, and catalyses the conversion of pyruvate to lactate in the semen of humans and other species ( Clausen and Ovlisen, 1965 ; Wilkinson and Withycombe, 1965 ; Coronel et al, 1983 ; LeVan and Goldberg, 1991 ; Wong et al, 1997 ; Hereng et al, 2011 ; Wang et al, 2016 ), which is crucial for glycolysis to continue production of adenosine triphosphate (ATP) ( Coronel et al, 1983 ; LeVan and Goldberg, 1991 ; Odet et al, 2011 ). LDH-C 4 , is the key factor of sperm glycolysis, which has an important role in sperm motility to provide ATP ( Coronel et al, 1983 ; Williams and Ford, 2001 ; Mukai and Okuno, 2004 ; Odet et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with LDH-A 4 and LDH-B 4 , LDH-C 4 had a lower K m for pyruvate (~0.052 mmol/L) and a higher K m for lactate (~4.934 mmol/L); thus, LDH-C 4 was less sensitive to lactate inhibition than LDH-A 4 and LDH-B 4 [47]. These properties of pika LDH-C 4 were beneficial for catalyzing the conversion of pyruvate to lactate even at a high concentration of lactate.…”
Section: Discussionmentioning
confidence: 99%